The increasingly anti-tumor effect of a colonic carcinoma DNA vaccine carrying HER2 by the adjuvanticity of IL-12. (1st November 2016) - Gao, Ping; Zhang, Chunhua; Bian, Xiaoxia; Guo, Yanjun; Wei, Yueguang; Zhang, Li; Liu, Zhaoyang; Wang, Xiuying; Huang, Shumin
Abstract: The present study aimed to determine the effect of recombinant DNA vaccine-based human epidermal growth factor receptor-2 (HER2) and Interleukin 12 (IL-12) on the development of colonic carcinoma in mice and the potential immune mechanisms involved. Recombinant plasmids pVAX1-HER2, pVAX1-IL-12 and pVAX1-HER2-IL-12 were constructed, and injected into female mice intramuscularly (i.m.) followed by an electric pulse. The humoral and cellular immune responses after immunization were examined by enzyme linked immunosorbent assay (ELISA) and enzyme-linked immunospot assay (ELISPOT), respectively. To evaluate the anti-tumor efficacy of the plasmids, a mouse model with a HER2-expressing tumor was designed. Mice vaccinated with the HER2-IL-12 plasmid generated the strongest inhibition efficacy on the growth of HER2-expressing tumors and prolonged mouse survival. These observations emphasized the potential of IL-12 as an adjuvant for DNA vaccines and of vaccines based on HER2 and IL-12 as a promising treatment for colonic carcinoma.